A preparation method of lithium iron phosphate and its application
During the preparation process of lithium iron phosphate material, hydrogel microspheres are used as templates for precipitation and freezing of iron phosphate to form a easily broken iron phosphate layer, which solves the problem of tight bonding of existing materials and realizes the preparation of lithium iron phosphate materials with small particle size and high reactive activity.
Patent Information
- Application Number
- CN202410191969.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-02-21
AI Technical Summary
The existing lithium iron phosphate materials are dense and bonded and difficult to break, making it difficult to obtain small particles, affecting the lithium ion diffusion path and battery performance.
By mixing sodium alginate, tanninic acid and iron hydroxide powder to form a suspension, and mixing it with oil to form an emulsion, adding an acid solution to react iron hydroxide to form hydrogel microspheres, and precipitation and freezing of iron phosphate as a template to form a easily broken iron phosphate layer, and then mixing with a lithium source and a carbon source to obtain a small-particle lithium iron phosphate material.
The lithium iron phosphate material is easily broken and loose, the material particle size and lithium ion diffusion path are reduced, and the battery's reactivity and rate performance are improved.
Smart Images

Figure CN118026134B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a preparation method of lithium iron phosphate and application thereof. Background Art
[0002] Lithium iron phosphate has the advantages of high theoretical capacity, high operating voltage and appropriate operating density, low self-discharge, long cycle life and good cycle performance. It is an ideal positive electrode material for the new generation of lithium-ion batteries and has been widely used in portable electronic products.
[0003] Lithium iron phosphate cathode materials have quickly occupied the current market due to their safety, environmental protection, high capacity, and high cost-effectiveness of raw materials. However, LiFePO4 is also controversial in the market due to its shortcomings such as low ion transmission rate and poor conductivity. The production of lithium iron phosphate is inseparable from crushing, which breaks coarse particles into very fine particles, increases their surface area, and greatly improves the utilization rate of raw materials. However, most of the lithium iron phosphate materials currently prepared are relatively dense and bonded, making it difficult to crush, and it is not easy to obtain small particles of lithium iron phosphate. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a preparation method of lithium iron phosphate and its application, which can prepare an easily broken and loose iron phosphate material, which is beneficial to the crushing process of lithium iron phosphate, reduces the particle size of the material, and thus reduces the diffusion path of lithium ions.
[0005] According to one aspect of the present invention, a method for preparing lithium iron phosphate is provided, comprising the following steps:
[0006] S1: mixing an oil substance with an emulsifier to obtain an oil phase; mixing sodium alginate, tannic acid and water to prepare a mixed solution, and adding iron hydroxide powder to the mixed solution to obtain a suspension;
[0007] S2: mixing the oil phase and the suspension to form an emulsion, adding an acid solution to react under stirring, separating the solid and the liquid to obtain hydrogel microspheres, and washing the hydrogel microspheres;
[0008] S3: dispersing the washed hydrogel microspheres in water, adding iron salt and phosphate, controlling the temperature and pH to perform a precipitation reaction of iron phosphate, and performing solid-liquid separation to obtain iron phosphate-coated hydrogel microspheres;
[0009] S4: freezing the iron phosphate-coated hydrogel microspheres, and then drying and calcining them to obtain anhydrous iron phosphate;
[0010] S5: mixing the anhydrous iron phosphate, lithium source, carbon source and supplemented phosphorus source, adding an organic solvent as a dispersant, grinding the obtained mixture, and then drying and calcining in the absence of oxygen to obtain the lithium iron phosphate.
[0011] Since iron hydroxide powder is added in step S1, the iron content in the anhydrous ferric phosphate is slightly higher, and a phosphorus source needs to be added. The anhydrous ferric phosphate, the lithium source and the added phosphorus source are added in a lithium, iron and phosphorus ratio of 1:1:1.
[0012] In some embodiments of the present invention, in step S1, the oil substance is at least one of liquid paraffin or vegetable oil.
[0013] In some embodiments of the present invention, in step S1, the emulsifier is at least one of polysorbate-20, polysorbate-80, Span-80, polyethylene glycol (200) monolaurate, lauric acid monoglyceride, polyglycerol fatty acid ester, polyethylene glycol (200) dilaurate, lauric acid diglyceride or sorbitan monolaurate.
[0014] In some embodiments of the present invention, in step S1, the mass volume ratio of the emulsifier to the oil substance is (0.2-0.8) g: 30 mL. An appropriate amount of emulsifier is conducive to forming stable microspheres. If the amount of emulsifier is too low, the system will be unstable and the hydrogel microspheres will become sticky.
[0015] In some embodiments of the present invention, in step S1, the concentration of sodium alginate in the mixed solution is 1.5wt%-2.5wt%; the concentration of tannic acid in the mixed solution is 0.2wt%-0.3wt%. The amount of sodium alginate should not be too much, otherwise it will easily cause the hydrogel microspheres to be elliptical, with low sphericity, and will become sticky.
[0016] In some embodiments of the present invention, in step S1, the mass ratio of the iron hydroxide powder to the sodium alginate is (4-6):9.
[0017] In some embodiments of the present invention, in step S2, the oil phase is mixed with the suspension and stirred for 15-30 minutes to form the emulsion. Furthermore, the mixing and stirring rate of the oil phase and the suspension is 500-800 rpm.
[0018] In some embodiments of the present invention, in step S2, the stirring rate is 500-800 rpm.
[0019] In some embodiments of the present invention, in step S2, the reaction time is 30-60 min.
[0020] In some embodiments of the present invention, in step S2, the volume ratio of the oil phase, the suspension and the acid solution is 1:(0.5-0.8):(0.2-0.5), and the concentration of the acid solution is 2-4 mol / L.
[0021] In some embodiments of the present invention, in step S2, the acid solution is a hydrochloric acid solution.
[0022] In some embodiments of the present invention, in step S2, the washing is: first washing with an emulsifier solution and then washing with water.
[0023] In some embodiments of the present invention, in step S3, the temperature of the precipitation reaction is controlled to be 50-80° C.; and the pH of the precipitation reaction is controlled to be 1.8-2.2.
[0024] In some embodiments of the present invention, in step S3, the precipitation reaction time is 4-6 hours.
[0025] In some embodiments of the present invention, in step S3, the volume ratio of the hydrogel microspheres to water is 1:(2-4).
[0026] In some embodiments of the present invention, in step S3, the iron salt is at least one of ferric chloride or ferric nitrate.
[0027] In some embodiments of the present invention, in step S3, the particle size of the iron phosphate-coated hydrogel microspheres is 15-35 μm.
[0028] In some embodiments of the present invention, in step S3, the phosphate is at least one of ammonium hydrogen phosphate, ammonium phosphate or diammonium phosphate.
[0029] In some embodiments of the present invention, in step S4, the temperature of the freezing treatment is -15 to -10°C; and the time of the freezing treatment is 1 to 2 hours.
[0030] In some embodiments of the present invention, in step S4, the drying temperature is 50-100° C., and the drying time is 8-10 h.
[0031] In some embodiments of the present invention, in step S5, the organic solvent is at least one of ethanol or propanol.
[0032] In some embodiments of the present invention, in step S5, the grinding time is 1-3 hours.
[0033] In some embodiments of the present invention, in step S5, the drying temperature is 60-70°C.
[0034] In some embodiments of the present invention, in step S5, the calcination temperature is 600-850° C.; the calcination atmosphere is an inert atmosphere; and the calcination time is 6-15 hours.
[0035] In some embodiments of the present invention, in step S5, the lithium source is at least one of lithium carbonate or lithium hydroxide.
[0036] In some embodiments of the present invention, in step S5, the carbon source is at least one of glucose, sucrose, polyethylene glycol, graphene, carbon powder or carbon black.
[0037] In some embodiments of the present invention, in step S5, the mass ratio of the anhydrous ferric phosphate to the carbon source is 1:(0.1-0.2).
[0038] In some embodiments of the present invention, in step S5, the phosphorus source is at least one of ammonium hydrogen phosphate, ammonium dihydrogen phosphate or ammonium phosphate.
[0039] In some embodiments of the present invention, in step S5, the particle size D50 of the lithium iron phosphate is 0.8-1.8 μm. Further, the particle size D50 of the lithium iron phosphate is 1.0-1.5 μm.
[0040] The invention also proposes the application of the preparation method in the preparation of lithium ion batteries.
[0041] According to the embodiments of the present invention, there are at least the following beneficial effects:
[0042] The invention adds a suspension containing sodium alginate, tannic acid and ferric hydroxide powder into an oil phase to form an oil-in-water emulsion, and then adds an acid solution to make the ferric hydroxide react under acidic conditions to generate trivalent iron ions, which interact with the sodium alginate and tannic acid to form hydrogel microspheres; the addition of tannic acid can increase the water content of the hydrogel microspheres, so that the hydrogel has a high water content and low solidity. Subsequently, the hydrogel microspheres are used as templates, and the adsorption property of the gel is utilized to adsorb iron ions on the surface of the hydrogel microspheres to form an iron phosphate layer with phosphate. The hydrogel microspheres coated with iron phosphate are frozen at low temperatures. Through the ice splitting effect, that is, the volume of water increases by 9% during the freezing process, and the volume increases during the phase change process, the iron phosphate layer generates an outward force from the inside, making the iron phosphate shell loose and easy to break. After heat drying, the iron phosphate layer becomes looser due to the evaporation of water and the shrinkage of the gel. The iron phosphate is then mixed with a lithium source and a carbon source and ground. During the grinding process, the iron phosphate is easily broken into small particles, which have a larger specific surface area, which is beneficial to improving the reaction activity, making the iron phosphate easier to react with the lithium source, improving the reaction rate and completeness, and small-particle lithium iron phosphate materials can also be directly obtained after calcination. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0044] Figure 1 This is a SEM image of the unbroken iron phosphate of Example 1 of the present invention. DETAILED DESCRIPTION
[0045] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0046] Example 1
[0047] This embodiment prepares a lithium iron phosphate, and the specific process is as follows:
[0048] (1) First, prepare the oil phase, add Span-80 to soybean oil at a mass volume ratio of 0.5 g: 30 mL, stir well and use as the oil phase; prepare the water phase, mix sodium alginate, tannic acid and water to prepare a mixed solution, wherein the mass fraction of sodium alginate is 2 wt%, the mass fraction of tannic acid is 0.25 wt%, then add Fe(OH)3 powder to the mixed solution, the mass ratio of Fe(OH)3 powder to sodium alginate is 5:9, stir well and obtain a suspension as the water phase;
[0049] (2) adding the aqueous phase to the oil phase and stirring continuously at 500 rpm for 30 min to form an emulsion, then adding 3 mol / L HCl solution, the volume ratio of the oil phase, the aqueous phase and the HCl solution is 1:0.8:0.2, stirring and reacting at 500 rpm for 30 min, filtering to obtain hydrogel microspheres, and then washing three times with a 10 wt % Span-80 aqueous solution, and then washing thoroughly with deionized water;
[0050] (3) The washed hydrogel microspheres were ultrasonically dispersed in deionized water at a volume ratio of 1:3, ferric chloride was added to make its concentration 1 mol / L, and after stirring, ammonium hydrogen phosphate was added to make its concentration 1 mol / L, and the iron-phosphorus ratio was 1:1, and stirred evenly. The reaction was carried out at 60° C. and pH 2.0 for 5 h, and the ferric phosphate was completely precipitated on the surface of the hydrogel microspheres. After filtering and washing, the ferric phosphate-coated hydrogel microspheres with a particle size distribution mainly in the range of 25-35 μm were obtained;
[0051] (4) placing the iron phosphate coated hydrogel microspheres in an environment at an ambient temperature of -12°C for 2 hours to obtain expanded iron phosphate coated hydrogel microspheres, heating the expanded iron phosphate coated hydrogel microspheres to 90°C at a rate of 2°C / min and drying them for 8 hours, and then calcining them at 600°C for 6 hours to obtain anhydrous iron phosphate;
[0052] (5) Anhydrous ferric phosphate, lithium carbonate and supplementary ammonium phosphate are mixed in a phosphorus, lithium and iron ratio of 1:1:1, and glucose is added at the same time. The mass ratio of anhydrous ferric phosphate to glucose is 1:0.15. Ethanol is added as a dispersant to obtain a mixed material. The mixed material is placed in a grinder and ground for 2 hours, and then placed in a drying oven at 60°C for drying. The dried mixed material is placed in a tubular furnace and calcined at 750°C for 10 hours in a nitrogen atmosphere to obtain a lithium iron phosphate material with D50=1.0μm.
[0053] Example 2
[0054] This embodiment prepares a lithium iron phosphate, and the specific process is as follows:
[0055] (1) First, prepare the oil phase, add Span-80 to soybean oil at a mass volume ratio of 0.5g:30mL, stir well and use as the oil phase; prepare the water phase, mix sodium alginate, tannic acid and water to prepare a mixed solution, wherein the mass fraction of sodium alginate is 2.5wt%, the mass fraction of tannic acid is 0.25wt%, then add Fe(OH)3 powder to the mixed solution, the mass ratio of Fe(OH)3 powder to sodium alginate is 5:9, stir well and obtain a suspension as the water phase;
[0056] (2) adding the aqueous phase to the oil phase and stirring continuously at 500 rpm for 30 min to form an emulsion, then adding 3 mol / L HCl solution, the volume ratio of the oil phase, the aqueous phase and the HCl solution is 1:0.8:0.2, stirring and reacting at 500 rpm for 30 min, filtering to obtain hydrogel microspheres, and then washing three times with a 10 wt % Span-80 aqueous solution, and then washing thoroughly with deionized water;
[0057] (3) ultrasonically dispersing the washed hydrogel microspheres in deionized water at a volume ratio of 1:3, adding ferric chloride to a concentration of 1 mol / L, stirring evenly, adding ammonium hydrogen phosphate to a concentration of 1 mol / L, and an iron-phosphorus ratio of 1:1, stirring evenly, reacting at 60°C and pH 2.0 for 5 hours, and ferric phosphate is completely precipitated on the surface of the hydrogel microspheres. After filtering and washing, iron phosphate-coated hydrogel microspheres with a particle size distribution mainly in the range of 20-35 μm are obtained;
[0058] (4) placing the iron phosphate coated hydrogel microspheres in an environment at an ambient temperature of -12°C for 2 hours to obtain expanded iron phosphate coated hydrogel microspheres, heating the expanded iron phosphate coated hydrogel microspheres to 90°C at a rate of 2°C / min and drying them for 8 hours, and then calcining them at 600°C for 6 hours to obtain anhydrous iron phosphate;
[0059] (5) Anhydrous ferric phosphate, lithium carbonate and supplementary ammonium phosphate are mixed in a phosphorus, lithium and iron ratio of 1:1:1, and glucose is added at the same time. The mass ratio of anhydrous ferric phosphate to glucose is 1:0.15. Ethanol is added as a dispersant to obtain a mixed material. The mixed material is placed in a grinder and ground for 2 hours, and then placed in a drying oven at 60°C for drying. The dried mixed material is placed in a tubular furnace and calcined at 750°C for 10 hours in a nitrogen atmosphere to obtain a lithium iron phosphate material with D50=1.1μm.
[0060] Example 3
[0061] This embodiment prepares a lithium iron phosphate, and the specific process is as follows:
[0062] (1) First, prepare the oil phase, add Span-80 to soybean oil at a mass volume ratio of 0.5g:30mL, stir well and use as the oil phase; prepare the water phase, mix sodium alginate, tannic acid and water to prepare a mixed solution, wherein the mass fraction of sodium alginate is 1.5wt%, the mass fraction of tannic acid is 0.25wt%, then add Fe(OH)3 powder to the mixed solution, the mass ratio of Fe(OH)3 powder to sodium alginate is 5:9, stir well and obtain a suspension as the water phase;
[0063] (2) adding the aqueous phase to the oil phase and stirring continuously at 500 rpm for 30 min to form an emulsion, then adding 3 mol / L HCl solution, the volume ratio of the oil phase, the aqueous phase and the HCl solution is 1:0.8:0.2, stirring and reacting at 500 rpm for 30 min, filtering to obtain hydrogel microspheres, and then washing three times with a 10 wt % Span-80 aqueous solution, and then washing thoroughly with deionized water;
[0064] (3) ultrasonically dispersing the washed hydrogel microspheres in deionized water at a volume ratio of 1:3, adding ferric chloride to a concentration of 1 mol / L, stirring evenly, adding ammonium hydrogen phosphate to a concentration of 1 mol / L, and an iron-phosphorus ratio of 1:1, stirring evenly, reacting at 60°C and pH 2.0 for 5 hours, and ferric phosphate is completely precipitated on the surface of the hydrogel microspheres. After filtering and washing, iron phosphate-coated hydrogel microspheres with a particle size distribution mainly in the range of 15-35 μm are obtained;
[0065] (4) placing the iron phosphate coated hydrogel microspheres in an environment at an ambient temperature of -12°C for 2 hours to obtain expanded iron phosphate coated hydrogel microspheres, heating the expanded iron phosphate coated hydrogel microspheres to 90°C at a rate of 2°C / min and drying them for 8 hours, and then calcining them at 600°C for 6 hours to obtain anhydrous iron phosphate;
[0066] (5) Anhydrous ferric phosphate, lithium carbonate and supplementary ammonium phosphate are mixed in a phosphorus, lithium and iron ratio of 1:1:1, and glucose is added at the same time. The mass ratio of anhydrous ferric phosphate to glucose is 1:0.15. Ethanol is added as a dispersant to obtain a mixed material. The mixed material is placed in a grinder and ground for 2 hours, and then placed in a drying oven at 60°C for drying. The dried mixed material is placed in a tubular furnace and calcined at 750°C for 10 hours in a nitrogen atmosphere to obtain a lithium iron phosphate material with D50=1.3μm.
[0067] Example 4
[0068] This embodiment prepares a lithium iron phosphate, and the specific process is as follows:
[0069] (1) First, prepare the oil phase, add Span-80 to soybean oil at a mass volume ratio of 0.2g:30mL, stir well and use as the oil phase; prepare the water phase, mix sodium alginate, tannic acid and water to prepare a mixed solution, wherein the mass fraction of sodium alginate is 2wt%, the mass fraction of tannic acid is 0.25wt%, then add Fe(OH)3 powder to the mixed solution, the mass ratio of Fe(OH)3 powder to sodium alginate is 5:9, stir well and obtain a suspension as the water phase;
[0070] (2) adding the aqueous phase to the oil phase and stirring continuously at 500 rpm for 30 min to form an emulsion, then adding 3 mol / L HCl solution, the volume ratio of the oil phase, the aqueous phase and the HCl solution is 1:0.8:0.2, stirring and reacting at 500 rpm for 30 min, filtering to obtain hydrogel microspheres, and then washing three times with a 10 wt % Span-80 aqueous solution, and then washing thoroughly with deionized water;
[0071] (3) The washed hydrogel microspheres were ultrasonically dispersed in deionized water at a volume ratio of 1:3, ferric chloride was added to make its concentration 1 mol / L, and after stirring, ammonium hydrogen phosphate was added to make its concentration 1 mol / L, and the iron-phosphorus ratio was 1:1, and stirred evenly. The reaction was carried out at 60° C. and pH 2.0 for 5 h, and the ferric phosphate was completely precipitated on the surface of the hydrogel microspheres. After filtering and washing, the ferric phosphate-coated hydrogel microspheres with a particle size distribution mainly in the range of 15-25 μm were obtained;
[0072] (4) placing the iron phosphate coated hydrogel microspheres in an environment at an ambient temperature of -12°C for 2 hours to obtain expanded iron phosphate coated hydrogel microspheres, heating the expanded iron phosphate coated hydrogel microspheres to 90°C at a rate of 2°C / min and drying them for 8 hours, and then calcining them at 600°C for 6 hours to obtain anhydrous iron phosphate;
[0073] (5) Anhydrous ferric phosphate, lithium carbonate and supplementary ammonium phosphate are mixed in a phosphorus, lithium and iron ratio of 1:1:1, and glucose is added at the same time. The mass ratio of anhydrous ferric phosphate to glucose is 1:0.15. Ethanol is added as a dispersant to obtain a mixed material. The mixed material is placed in a grinder and ground for 2 hours, and then placed in a drying oven at 60°C for drying. The dried mixed material is placed in a tubular furnace and calcined at 750°C for 10 hours in a nitrogen atmosphere to obtain a lithium iron phosphate material with D50=1.5μm.
[0074] Example 5
[0075] This embodiment prepares a lithium iron phosphate, and the specific process is as follows:
[0076] (1) First, prepare the oil phase, add Span-80 to soybean oil at a mass volume ratio of 0.8 g: 30 mL, stir well and use as the oil phase; prepare the water phase, mix sodium alginate, tannic acid and water to prepare a mixed solution, wherein the mass fraction of sodium alginate is 2 wt%, the mass fraction of tannic acid is 0.25 wt%, then add Fe(OH)3 powder to the mixed solution, the mass ratio of Fe(OH)3 powder to sodium alginate is 5:9, stir well and obtain a suspension as the water phase;
[0077] (2) adding the aqueous phase to the oil phase and stirring continuously at 500 rpm for 30 min to form an emulsion, then adding 3 mol / L HCl solution, the volume ratio of the oil phase, the aqueous phase and the HCl solution is 1:0.8:0.2, stirring and reacting at 500 rpm for 30 min, filtering to obtain hydrogel microspheres, and then washing three times with a 10 wt % Span-80 aqueous solution, and then washing thoroughly with deionized water;
[0078] (3) The washed hydrogel microspheres were ultrasonically dispersed in deionized water at a volume ratio of 1:3, ferric chloride was added to make its concentration 1 mol / L, and after stirring, ammonium hydrogen phosphate was added to make its concentration 1 mol / L, and the iron-phosphorus ratio was 1:1, and stirred evenly. The reaction was carried out at 60° C. and pH 2.0 for 5 h, and the ferric phosphate was completely precipitated on the surface of the hydrogel microspheres. After filtering and washing, the ferric phosphate-coated hydrogel microspheres with a particle size distribution mainly in the range of 25-35 μm were obtained;
[0079] (4) placing the iron phosphate coated hydrogel microspheres in an environment at an ambient temperature of -12°C for 2 hours to obtain expanded iron phosphate coated hydrogel microspheres, heating the expanded iron phosphate coated hydrogel microspheres to 90°C at a rate of 2°C / min and drying them for 8 hours, and then calcining them at 600°C for 6 hours to obtain anhydrous iron phosphate;
[0080] (5) Anhydrous ferric phosphate, lithium carbonate and supplementary ammonium phosphate are mixed in a phosphorus, lithium and iron ratio of 1:1:1, and glucose is added at the same time. The mass ratio of anhydrous ferric phosphate to glucose is 1:0.15. Ethanol is added as a dispersant to obtain a mixed material. The mixed material is placed in a grinder and ground for 2 hours, and then placed in a drying oven at 60°C for drying. The dried mixed material is placed in a tubular furnace and calcined at 750°C for 10 hours in a nitrogen atmosphere to obtain a lithium iron phosphate material with D50=1.0μm.
[0081] Comparative Example 1
[0082] This comparative example prepares a lithium iron phosphate, which is different from Example 1 in that the lithium iron phosphate is directly prepared without using hydrogel balls. The specific process is as follows:
[0083] (1) preparing a mixed solution of ferric chloride and ammonium hydrogen phosphate, wherein the concentration of ferric chloride and ammonium hydrogen phosphate is 1 mol / L, reacting for 5 hours at 60° C. and pH 2.0 to completely precipitate ferric phosphate, filtering, and drying to obtain ferric phosphate;
[0084] (2) placing the iron phosphate in an environment at an ambient temperature of -12°C for 2 hours, heating the frozen iron phosphate to 90°C at a rate of 2°C / min and drying it for 8 hours, and then calcining it at 600°C for 6 hours to obtain anhydrous iron phosphate;
[0085] (3) Anhydrous ferric phosphate and lithium carbonate were mixed in a ratio of 1:1:1 for phosphorus, lithium and iron, and then glucose was added as a carbon source. The mass ratio of anhydrous ferric phosphate to glucose was 1:0.15. Ethanol was used as a dispersant for mixing. The mixed material was placed in a grinder and ground for 2 hours. Then, it was placed in a drying oven at 60°C for drying. The dried mixed material was placed in a tubular furnace and calcined at 750°C for 10 hours in a nitrogen atmosphere to obtain a lithium iron phosphate material with D50=4.2μm.
[0086] Comparative Example 2
[0087] This comparative example prepares a lithium iron phosphate, which differs from Example 1 in that no freezing treatment is performed. The specific process is as follows:
[0088] (1) First, prepare the oil phase, add Span-80 to soybean oil at a mass volume ratio of 0.5 g: 30 mL, stir well and use as the oil phase; prepare the water phase, mix sodium alginate, tannic acid and water to prepare a mixed solution, wherein the mass fraction of sodium alginate is 2 wt%, the mass fraction of tannic acid is 0.25 wt%, then add Fe(OH)3 powder to the mixed solution, the mass ratio of Fe(OH)3 powder to sodium alginate is 5:9, stir well and obtain a suspension as the water phase;
[0089] (2) adding the aqueous phase to the oil phase and stirring continuously at 500 rpm for 30 min to form an emulsion, then adding 3 mol / L HCl solution, the volume ratio of the oil phase, the aqueous phase and the HCl solution is 1:0.8:0.2, stirring and reacting at 500 rpm for 30 min, filtering to obtain hydrogel microspheres, and then washing three times with a 10 wt % Span-80 aqueous solution, and then washing thoroughly with deionized water;
[0090] (3) The washed hydrogel microspheres were ultrasonically dispersed in deionized water at a volume ratio of 1:3, ferric chloride was added to make its concentration 1 mol / L, and after stirring, ammonium hydrogen phosphate was added to make its concentration 1 mol / L, and the iron-phosphorus ratio was 1:1, and stirred evenly. The reaction was carried out at 60° C. and pH 2.0 for 5 h, and the ferric phosphate was completely precipitated on the surface of the hydrogel microspheres. After filtering and washing, the ferric phosphate-coated hydrogel microspheres with a particle size distribution mainly in the range of 25-35 μm were obtained;
[0091] (4) heating the hydrogel microspheres coated with iron phosphate to 90° C. at a rate of 2° C. / min and drying them for 8 h, and then calcining them at 600° C. for 6 h to obtain anhydrous iron phosphate;
[0092] (5) Anhydrous ferric phosphate, lithium carbonate and supplementary ammonium phosphate were mixed in a phosphorus, lithium and iron ratio of 1:1:1, and glucose was added at the same time. The mass ratio of anhydrous ferric phosphate to glucose was 1:0.15. Ethanol was added as a dispersant to obtain a mixed material. The mixed material was placed in a grinder and ground for 2 hours, and then placed in a drying oven at 60°C for drying. The dried mixed material was placed in a tubular furnace and calcined at 750°C for 10 hours in a nitrogen atmosphere to obtain a lithium iron phosphate material with D50 = 3.2 μm.
[0093] Test example
[0094] The binder and the conductive agent were mixed with the LiFePO4 powder of the embodiment and the comparative example at a mass ratio of 1:1:8, and N-methylpyrrolidone was added to make a slurry, which was evenly coated on an aluminum foil, vacuum dried, rolled and punched into a circular electrode sheet, and assembled into a button battery in a glove box. The button battery was tested for constant current charge and discharge cycles, and the charge and discharge voltage was 2.5-4.2V. The embodiment and the comparative example were tested at a rate specific capacity of 0.2C, 3C and 10C, and the results are shown in Table 1.
[0095] Table 1 Rate performance
[0096] sample 0.2C 3C 5C 10C Example 1 163 155 146 136 Example 2 159 150 141 132 Example 3 162 154 144 135 Example 4 157 148 139 126 Example 5 161 153 140 130 Comparative Example 1 146 135 124 109 Comparative Example 2 155 143 132 120
[0097] As can be seen from Table 1, the rate performance of Comparative Example 1 and Comparative Example 2 are not as good as that of Example 1. This is because Comparative Example 1 adopts a conventional iron phosphate precipitation method, and the product formed is a large and dense agglomerate, which is difficult to crush. The particle size of the final lithium iron phosphate material is relatively large, which limits the ion transfer rate, resulting in a decrease in the performance of the battery during high-rate charge and discharge. The rate performance of Comparative Example 2 is slightly higher than that of Comparative Example 1 but still not as good as that of Example 1. This is because the iron phosphate layer of Comparative Example 2 has not undergone freezing expansion, and the structure is denser than that of Example 1, and it is not easy to crush. However, although Comparative Example 2 has not undergone freezing treatment, it still has a hollow structure formed with the gel as a template, and the crushing difficulty is lower than that of the solid and dense Comparative Example 1, and the hollow structure has a higher specific surface area, so the rate performance is also slightly higher than that of Comparative Example 1.
[0098] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing lithium iron phosphate, characterized in that: The following steps are involved: S1: mixing an oil substance with an emulsifier to obtain an oil phase; mixing sodium alginate, tannic acid and water to prepare a mixed solution, and adding iron hydroxide powder to the mixed solution to obtain a suspension; S2: mixing the oil phase and the suspension to form an emulsion, adding an acid solution to react under stirring, separating the solid and the liquid to obtain hydrogel microspheres, and washing the hydrogel microspheres; S3: dispersing the washed hydrogel microspheres in water, adding iron salt and phosphate, controlling the temperature and pH to perform a precipitation reaction of iron phosphate, and performing solid-liquid separation to obtain iron phosphate-coated hydrogel microspheres; S4: freezing the iron phosphate-coated hydrogel microspheres, and then drying and calcining them to obtain anhydrous iron phosphate; S5: mixing the anhydrous iron phosphate, lithium source, carbon source and supplemented phosphorus source, adding an organic solvent as a dispersant, grinding the obtained mixture, and then drying and calcining in the absence of oxygen to obtain the lithium iron phosphate; In step S1, the mass ratio of the iron hydroxide powder to the sodium alginate is (4-6):9; In step S2, the volume ratio of the oil phase, the suspension and the acid solution is 1:(0.5-0.8):(0.2-0.5), and the concentration of the acid solution is 2-4 mol / L; In step S3, the volume ratio of the hydrogel microspheres to water is 1:(2-4); In step S4, the temperature of the freezing treatment is -15 to -10°C; the time of the freezing treatment is 1 to 2 hours.
2. The preparation method according to claim 1, characterized in that: In step S1, the oil substance is at least one of liquid paraffin or vegetable oil.
3. The preparation method according to claim 1, characterized in that: In step S1, the emulsifier is at least one of polysorbate-20, polysorbate-80, Span-80, polyethylene glycol (200) monolaurate, lauric acid monoglyceride, polyglycerol fatty acid ester, polyethylene glycol (200) dilaurate, lauric acid diglyceride or sorbitan monolaurate.
4. The preparation method according to claim 1, characterized in that: In step S1, the mass volume ratio of the emulsifier to the oil substance is (0.2-0.8) g:30 mL.
5. The preparation method according to claim 1, characterized in that: In step S1, the concentration of sodium alginate in the mixed solution is 1.5wt%-2.5wt%; the concentration of tannic acid in the mixed solution is 0.2wt%-0.3wt%.
6. The preparation method according to claim 1, characterized in that: In step S2, the washing is: first washing with an emulsifier solution and then washing with water.
7. Use of the preparation method according to any one of claims 1 to 6 in the preparation of lithium ion batteries.
Citation Information
Patent Citations
Method for synthesizing lithium iron phosphate anode material by adopting emulsion liquid phase
CN102867954A
Method for preparing polymer microspheres by taking ferric hydroxide colloid as emulsion-method water phase
CN106668868A